Genome-Wide Association Study for Nodule Traits in Guar - Shubham Malani; Waltram Ravelombola; Aurora Manley; Hanh Pham; Madeline Brown; Md. Mezanur Rahman (Current Issues in Molecular Biology)
Guar [Cyamopsis tetragonoloba (L.) Taub] is a diploid legume crop cultivated for galactomannan (guar gum) extracted from the endosperm of the seed. Previous studies have suggested that nodulation of guar can be poor in field conditions; however, solid proof has yet to be provided. The objectives of this study were to conduct a genome-wide association study (GWAS) and to identify single nucleotide polymorphism (SNP) markers associated with nodules in guar. GWAS was performed on a total of 225 guar genotypes using 19,007 filtered SNPs. Tassel 5 was used to run five models: single marker regression (SMR), generalized mixed linear model with PCA as a covariate (GLM_PCA), generalized mixed linear model with Q matrix as a covariate (GLM_Q), mixed linear model with PCA and Kinship (K) as covariates (GLM_PCA + K), and mixed linear model with Q and K as covariates (MLM_Q + K). Across all statistical models, the results showed a total of 3, 2, 25, 7, 2, and 3 SNPs were associated with plant height, nodule number per plant, fresh nodule weight, dry nodule weight, fresh aboveground plant biomass, and dry aboveground plant biomass. These SNPs could be used as a tool to select for better nodule traits in guar.